Comparative Study on Recovery and Post-Operative Analgesic Efficacy from Fentanyl- Versus Dexmedetomidine-Based Anesthesia in Head and Neck Cancer Surgery - Liza Mohanty; Ravi Kumar; Deepak Tugave; Anagha Agrawal; Sejal Patel; Monika Tanwar; Lalit Patil (Journal of Pharmacy and Bioallied Sciences)
Background: Effective post-operative analgesia and swift recovery are critical for patients undergoing head and neck cancer surgery. This study compares the recovery profiles and analgesic efficacy of fentanyl-based anesthesia versus dexmedetomidine-based anesthesia in this patient population. Materials and Methods: A randomized controlled trial was conducted with 120 patients undergoing head and neck cancer surgery. The patients were divided into two groups: Group F (n = 60) received fentanyl-based anesthesia, while Group D (n = 60) received dexmedetomidine-based anesthesia. Recovery profiles were assessed using the Modified Aldrete Score, and post-operative pain was evaluated using the Visual Analog Scale (VAS) at 1, 6, 12, and 24 hours post-surgery. Secondary outcomes included total opioid consumption and the incidence of adverse effects. Results: Group D demonstrated a significantly faster recovery time, with 85% achieving a Modified Aldrete Score of ≥9 within 30 minutes post-surgery compared to 65% in Group F (P < 0.05). Post-operative VAS scores were significantly lower in Group D at all time points (P < 0.01), with mean scores of 2.5 ± 1.2 at 1 hour, 2.0 ± 1.0 at 6 hours, 1.5 ± 0.8 at 12 hours, and 1.0 ± 0.5 at 24 hours. Group F had mean scores of 4.0 ± 1.5, 3.5 ± 1.3, 3.0 ± 1.1, and 2.5 ± 0.9, respectively. Total opioid consumption was also lower in Group D (50 mg morphine equivalents) compared to Group F (75 mg morphine equivalents) (P < 0.05). Adverse effects were comparable between the groups. Conclusion: Dexmedetomidine-based anesthesia provides superior post-operative analgesia and faster recovery compared to fentanyl-based anesthesia in head and neck cancer surgery. It may be a preferred option for optimizing patient outcomes in this surgical population.